Analisis Yuridis tentang Penghapusan Presidential Threshold dan Dampaknya Terhadap Sistem Pemilihan Presiden Republik Inodnesia (Studi Kasus: Putusan MK Nomor 62/PUU-XXII/2024) - Thalia Christine (CV Rewang Rencang, 2024)
The Constitutional Court Decision No. 62/PUU-XXII/2024 annulled the presidential threshold for nominating presidential and vice-presidential candidates. This research employs a normative juridical method with statutory, case, and conceptual approaches. The findings reveal that the abolition broadens political access, promotes equality, and supports a more inclusive democracy. The Court ruled that the threshold contradicts constitutional values and the principle of popular sovereignty.